Internationalization strategy of Quidgest to the Dominican Republic - Lavrador, Maria Ana Reis Moreira Mascarenhas (2019)
The underlying project was carried out with the purpose of conducting an internationalization strategy of Quidgest to the Dominican Republic. Thus, an analysis of the enterprise competitive advantages resources is computed, followed by a country ranking analysis to select the optical market. By evaluating both macro and industry indicators, it was concluded that the Dominican Republic was the most attractive country. Furthermore, an implementation strategy is suggested with the most favorable entry mode and several activities that need to take place in order to complete a successful internationalization process.